CIRCULARLY POLARIZED PERIODIC LEAKY-WAVE ANTENNA BASED ON A COAXIAL LINE WITH HELICAL SLOT (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
A novel coaxial-line-based helical leaky-wave antenna (LWA) with circular polarization (CP) is presented in this work. The CP is achieved thanks to a helical-shaped slot edged on the outer conductor of the coaxial line that allows for controlled radiation when the fundamental TEM mode of the coaxial line is fed. Thus, a periodic-like LWA is formed with frequency-scanning of a conical beam and suppressed open stopband achieved thanks to the continuous radiation along the helical slot. This way, the radiation efficiency can be kept high in a wide scanning range. A prototype has been designed and manufactured for validation with beam scanning from -90° to 12° in the 8-16 GHz frequency range. The efficiency is above 75 % in almost all this frequency band with a simulated axial ratio below 3 dB, showing proper CP performance.